AB0700 GOLIMUMAB PERSISTENCE IN BIOLOGIC NAÏVE AND NON-NAÏVE PATIENTS WITH AXIAL SPONDYLOARTHRITIS: RESULTS OF THE GO-PRACTICE STUDY. (June 2019) - Bertin, Philippe; Goupille, Philippe; Tubach, Florence; Ouaniche, Jean; Lespessailles, Eric; Gouyette, Najat; Harid, Naoual; Fayette, Jean-Marie; Fautrel, Bruno; Flipo, René-Marc
Abstract : Background: Golimumab (GLM ) was the latest anti-TNFα therapy to be indicated in the treatment of chronic inflammatory rheumatic diseases. The pivotal GO-AFTER study [1 ] and the ongoing observational GO-BEYOND study investigate GLM efficacy in rheumatoid arthritis (RA ) patients who previously received biologics. However, clinical studies of GLM in axial spondyloarthritis (AS ) are lacking. Using data from the GO-PRACTICE study, we examined GLM persistence in patients with aS. Objectives: Primary objective was to estimate GLM persistence at 2 years from initial prescription, as a first line of treatment (in biologic naïve patients:BN ) and as a second or further line of treatment (in biologic pretreated patients:BP ). Persistence was estimated with the Kaplan-Meier method. Secondary outcomes included assessing disease activity (ASDAS ) evolution and patient-reported evaluations of disease activity (BASDAI ), pain (VAS ), functional ability (HAQ ) and quality of life (EQ-5D and SF-12 ). Methods: Observational, prospective, multicenter French study, that recruited adult patients with RA, psoriatic arthritis or aS, who were newly prescribed GLM. Patients were followed-up over 2 years; data were collected at baseline (BL ), 1 year and 2 years. This abstract presents results from the aS cohort of GO-PRACTICE. Results: 478 patients with aS (constituting 63% of the total cohort) from 134 sites were included from January 2015 to March 2016. Mean age was 43 years, 55% were female; 61% were BN (n=291) and 39% (n=187) were BP. Mean duration of aS was 5.5 and 10.7 years in BN and BP patients, respectively ( P <.001). At BL most were prescribed 50 mg GLM monthly (97%). Co-treatments were disease-modifying anti-rheumatic drugs (34%), corticosteroids (17%) and NSAIDs/analgesics (90%). GLM persistence over 2 years was significantly higher in BN than BP patients (59.2% vs 45.1%, p <.01). For those still on GLM at 2 years, disease activity (Table1 ) and patient assessments showed significant improvements for both, BN and BP patients, with improvements being greater in BN patients. GLM was well tolerated in aS patients (n=478), with 46 (9.6%) discontinuing due to intolerance. Among BN patients, 18 (6.2%) discontinued GLM due to primary treatment failure, compared to 28 BP patients (15%). GLM was re-prescribed for 213 (88%) of the 241 patients persisting on GLM at 2-years. Post-hoc multivariate analysis showed that being female was a risk factor for GLM discontinuation in aS patients (HR1.9, IC95% 1.4-2.6). Conclusion: GLM is associated with clinical improvements and good persistence in aS patients, especially those who are biologic naïve. References: [1] Smolen JS, et al; arthritis research & therapy2015, 17:14 Disclosure of interests: Philippe Bertin Grant/research support from: Financial compensation received from MSD on a pro-rota basis for participation in Scientific Committee meetings and functions for this study, Philippe Goupille Grant/research support from: Financial compensation received from MSD on a pro-rota basis for participation in Scientific Committee meetings and functions for this study, Speakers bureau: abbvie, Biogaran, BMS, Hospira, Janssen, MSD, Pﬁzer, Sanoﬁ-Genzyme, UCB, Florence Tubach Grant/research support from: Financial compensation received from MSD on a pro-rota basis for participation in Scientific Committee meetings and functions for this study, Jean OUANICHE Grant/research support from: Financial compensation received from MSD on a pro-rota basis for active participation in Scientific Committee meetings and functions, Eric Lespessailles Grant/research support from: Grants/research support from amgen, Eli Lily, MSD, UCB., Consultant for: Consultant for amgen, Expanscience, Eli Lilly, MSD, UCB., Najat Gouyette Employee of: MSD, France, Naoual HARID Employee of: MSD, France, jean-marie Fayette Consultant for: Contract Research Organisation - ClinSearch, Bruno Fautrel Grant/research support from: abbVie, Lilly, MSD, Pfizer, Consultant for: abbVie, Biogen, BMS, Celgene, Janssen, Lilly, Medac, MSD, NORDIC Pharma, Novartis, Pfizer, Roche, Sanofi-Aventis, Sanofi Genzyme, SOBI, UCB, René-Marc Flipo Consultant for: Honoraria from Novartis as steering committe of this survey